Insect-repellent and mosquitocidal effects of noreremophilane- and nardoaristolone-based compounds - Handore, K. L.; Kalmode, H. P.; Sayyad, S.; Seetharamsingh, B.; Gathalkar, G.; Padole, S.; Pawar, P. V.; Joseph, M.; Sen, A.; Reddy, D. S. (ACS Omega, 2019)
Here, we disclose novel mosquito-repellent synthetic hydrindanes based on noreremophilanes and nardoaristolone B which show increased activity against adult females of Aedes aegypti. The noreremophilanes and nardoaristolone B with hydrindane skeleton are structurally related to nootkatone with decalin skeleton, a well-studied natural product extracted from a grape fruit. Out of our library of compounds synthesized based on the noreremophilanes and nardoaristolone B scaffolds, NDS-100598 (compound 20) exhibits higher repellent and knock-down effects at a very low concentration (0.25 mg/cm2), while a few analogues showed considerably enhanced activity compared to racemic nootkatone. This is the first report documenting insect-repellent and knock-down activity of the noreremophilanes class of compounds.